1983
DOI: 10.1159/000198880
|View full text |Cite
|
Sign up to set email alerts
|

Gut and Pancreatic Hormones after Jejunoileal Bypass with 3:1 or 1:3 Jejunoileal Ratio

Abstract: The aim of the study was to elucidate the differential role of the jejunum and ileum in the regulation of secretion of the gut hormones, gastrin, gastric inhibitory polypeptide, and enteroglucagon, and the pancreatic hormones, insulin, glucagon, and pancreatic polypeptide, in man. We measured the plasma levels of the hormones (and glucose) during fasting and after a test meal in 34 obese patients, of whom 5 were waiting for bypass surgery and 29 had had a jejunoileal bypass with a 3:1 or 1:3 jejunoileal ratio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

1983
1983
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 17 publications
2
14
0
Order By: Relevance
“…Following obesity surgery, there is no evidence of an increased release (Table 2) ( [77,78] and Le Roux CW, Aylwin SJB, Bloom SR, unpublished data).…”
Section: Effect Of Bariatric Surgery On Gi Hormones That Inhibit Appementioning
confidence: 99%
“…Following obesity surgery, there is no evidence of an increased release (Table 2) ( [77,78] and Le Roux CW, Aylwin SJB, Bloom SR, unpublished data).…”
Section: Effect Of Bariatric Surgery On Gi Hormones That Inhibit Appementioning
confidence: 99%
“…We do not agree that subtraction of the C-terminal ('pancreatic') immunoreactivity from N-terminal-to-central ('total') immuno reactivity [3,37] gives an accurate measure ment of gut glucagon precursors since some material larger than glucagon, which binds only the latter type (N-terminal-to-central) of antibody, is found in the pancreas and is released into the circulation following argi nine stimulation [11,26]. Also, material which binds C-terminal antibodies may be released from the lower gut or formed follow ing the release of larger gut precursors by pro teolytic catabolism [25,26,30].…”
Section: Discussionmentioning
confidence: 71%
“…This contrast, together with the tendency for the non-func tional ileum to contain slightly more rather than less YY57 immunoreactivity, is not in dicative of a major hypertrophic or other role [3,7,16,35,37] for large glucagon precur sors) in the morphological changes which follow the operations. Dawson et al [7] re ported that the ileal enteroglucagon immuno reactivity was unchanged in the functional ileum of patients who had extensive JIB operations.…”
Section: Discussionmentioning
confidence: 82%
“…Intestinal resection provokes the hypersecretion of gastric acid, probably by increasing gastrin production [1,12,28]. Sorensen et al [20] and Dawson et al [5] found that bypass surgery has no important influence on the levels of gastrin produced. Junghanns et al [10] reported a less pronounced rise of serum gastrin levels after distal resection than after proximal resection (PR) in dogs.…”
Section: Discussionmentioning
confidence: 99%